(3HQfGeL ebJQM bGFe Ydi JSQjY Gdfeh GdeYQai dJfejI GdJMUjd ai eGOI GdcjejGA h GdOGaYjI ddJYde h HYV egGQGJ GdJacjQ dOi WdGH GdeQMdI GdKGfhjI (B= s A suggested program based on cognitive acceleration in developing achievement in chemistry, learning motivation, and some thinking skills among secondary stage students - (3TjeGA MSfjf CMeO MSfjfs; (3CeGfi SYjOg SjO EHQGgje (B: s; (3CeGfi eMeO SYO GdOjf GdehLi (B: s ((3GdbGgQI (B: s (3TjeGA MSfjf CMeO MSfjf (B: s, 2019)
(3gPG GdHMK JYQa aGYdjI HQfGeL ebJQM bGFe Ydi JSQjY Gdfeh GdeYQai dJfejI GdJMUjd ai eGOI GdcjejGA h GdOGaYjI ddJYde h HYV egGQGJ GdJacjQ dOi WdGH GdeQMdI GdKGfhjI(B: (3h dJMbjb gPG GdgOa(B: (3GSJNOeJ GdHGMKI GdefgL GdJLQjHj MjK JchfJ eLehYI GdHMK ef (B80 (3WGdHI ef WGdHGJ GdUa GdChd GdKGfhi Je JbSjegef Edi eLehYJjf EMOGgeG JLQjHjI JchfJ ef (B40 (3WGdHI OQSJ HGdHQfGeL GdebJQM(B: (3h GdCNQi VGHWI JchfJ ef (B40 (3WGdHI OQSJ HGdWQjbI GdJbdjOjI(B: (3h Je HfGA ENJHGQ JMUjdi dhMOI (B"(3GdeMGdjd h GdCMeGV h GdbhGYO h GdCedGM(B": (3h ebjGS GdOGaYjI dJYde GdcjejGA(B: (3h ebjGS egGQGJ GdMd GdEHOGYi ddeTcdGJ(B: (3MjK Je JWHjbge bHdjkG h HYOjkG Ydi eLehYJi GdHMK(B: (3h CSaQJ GdfJGFL Yf hLhO aQhb PGJ OdGdI EMUGFjI Hjf eJhSWGJ OQLGJ WGdHGJ GdeLehYJjf GdJLQjHjI h GdVGHWI ai GdENJHGQ GdJMUjdi h ebjGS GdOGaYjI dJYde GdcjejGA(B: (3h ebjGS egGQGJ GdMd GdEHOGYi ddeTcdGJ ai GdJWHjb GdHYOi dUGdM GdeLehYI GdJLQjHjI(B: (3h cPdc CTGQJ GdfJGFL Edi aGYdjI GdHQfGeL GdebJQM ai JfejI GdJMUjd h GdOGaYjI dJYde GdcjejGA(B: (3h egGQGJ GdMd GdEHOGYi ddeTcdGJ dOi WGdHGJ GdUa GdChd GdKGfhis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe GdefGgL h WQb GdJOQjSs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdOGaYjI ddJYdes; (3HQfGeL ebJQM bGFe Ydi JSQjY Gdfeh GdeYQais; (3egGQGJ GdMd GdEHOGYi ddeTcdGJs